Shen-Zhi-Ling Oral Liquid Improves Behavioral and Psychological Symptoms of Dementia in Alzheimer's Disease. (18th May 2014) - Pan, Weidong; Wang, Qiudong; Kwak, Shin; Song, Yu; Qin, Baofeng; Wang, Mingzhe; Yamamoto, Yoshiharu
Abstract : We evaluated the effects of the traditional Chinese medicine (TCM) Shen-Zhi-Ling oral liquid (SZL) on the behavioral and psychological symptoms of dementia (BPSD) in patients with Alzheimer's disease (AD). Among 98 patients with AD and BPSD enrolled (mean age, 57.2 ± 8.9 years old), 91 ( M = 55, F = 36; mean age, 57.2 ± 9.7 years old) completed the study. Patients took either SZL (n = 45 ) or placebo granules (n = 46 ) in a double-blind manner for 20 weeks while maintaining other anticognitive medications unchanged. Changes in BPSD between week 0, week 10, week 20, and week 25 were assessed using the behavioral pathology in Alzheimer's disease (BEHAVE-AD) rating scale and the neuropsychiatric inventory (NPI), detrended fluctuation analysis (DFA) represented by diurnal activity (DA), evening activity (EA), and nocturnal activity (NA) according to actigraphic recordings. SZL but not placebo oral liquid delayed the development of BPSD significantly according to the changes in some of the clinical scores and the EA and NA parameters of DFA at week 20 compared with week 0. No side effects were observed in laboratory tests. The results indicate that SZL might delay the development of BPSD in AD patients and thus is a potentially suitable drug for long-term use.